Proxy and self-reported Quality of Life in adults with intellectual disabilities: Impact of psychiatric symptoms, problem behaviour, psychotropic medication and unmet needs. (October 2015) - Koch, Andrea D.; Vogel, Anke; Becker, Thomas; Salize, Hans-Joachim; Voss, Elke; Werner, Amelie; Arnold, Katrin; Schützwohl, Matthias
Highlights: Self-rated and proxy rated QoL of adults with intellectual disability was compared. Proxy reports of QoL were consistently lower than QoL self-reports. Agreement between self and proxy reports was poor to fair in all QoL domains. The effect of four predictors on self-rated and proxy rated QoL was analyzed. A reduction of unmet needs and of psychotropic medication positively affect QoL. Abstract: Proxies often underestimate the subjective Quality of Life (QoL) of adults with intellectual disability (ID). However, little is known about the reasons for these differences. Accordingly, the purpose of the present study is to, firstly, compare the self-reported QoL of adults with ID with proxy reports from staff of sheltered working and housing facilities, and, secondly, to identify possible differences of the impact of four potential predictor variables. Data of 102 adults with ID were collected as part of the MEMENTA study ('Mental health care provision for adults with ID and a mental disorder'). Results show that self-report QoL scores ranged from 72.6 to 86.8. Both proxies consistently reported lower QoL scores and agreement between self and proxy ratings was predominantly poor. Unmet needs and psychotropic medication were identified as the most important predictors of reduced self-rated QoL, whereas an increase of psychiatric symptoms, problem behaviours, and psychotropic medication best predicted the reduced QoL proxy ratings. To conclude, proxies still have to strive for a more holistic approach in surrogate QoL assessments and according to adults with ID, service providers should focus on a reduction of unmet needs and psychotropic medication to further improve QoL.